A research on electrochemical salt-free dyeing with KN reactive dyes: process optimization studies. Issue 4 (3rd April 2017) - Fan, Zenglu; Cai, Xinbin; Li, Qing
Abstract: Four types of KN-type reactive dyes, C.I.Reactive Blue 19, C.I.Reactive Violet 5, C.I.Reactive Red 111, and C.I.Reactive Blue 21, were employed to study the dyeing process in electrochemical route. Effects of the applied voltage, the amount of anionic groups (sulfuric group) in the molecular structure of the dyes, dyeing temperature, dying time, fixation time were studied to explore the optimum process parameters in lab. The results showed that K/S values of the fabric dyed with C.I.Reactive Blue 19, C.I.Reactive Violet 5, and C.I.Reactive Blue 21were increased than those of the conventional route by 3.6, 9.4, and 12.6%, respectively, under the optimum conditions. Meanwhile, COD values of the dyeing raffinate were reduced by 37.89, 45.67, and 52%, respectively, while the fastness properties had no remarkable differences from traditional dyeing.